From perception to payment: How cultural ecosystem services drive tourists' willingness to pay for ecological compensation in urban forest parks - Yupei Liang; Yajun Wang; Na Gao; Minhui Lin (Urban Forestry & Urban Greening, 2026)

PRMT1-rich exosomes derived from M2 macrophages as novel therapeutics for enhancing fracture healing - Haifeng Hong; Cuiyun Zhou; Haibing Wang; Changhui Lin; Min Fang; Juntian Liu; Minhui Yang (Tissue and Cell, 2026)

An Empirical Test of Scale‐Dependence of β‐Diversity in a Large Temperate Forest Region - Liqi Lu; Philip S. Barton; Senxuan Lin; Minhui Hao; Chunyu Fan; Klaus von Gadow; Xiuhai Zhao; Chunyu Zhang (Journal of Biogeography, 2026)
Aim Variation in species composition among locations (β‐diversity) is of fundamental interest in ecology, yet its dependence on spatial extent and grain has rarely been assessed empirically. This study provides a systematic empirical test of the spatial scaling of β‐diversity and highlights the importance of study design for detecting the role of environmental filtering in shaping regional β‐diversity. Location Northeastern China. Taxon Tree in forest ecosystems. Methods We constructed regional communities to define six gradients of spatial extent and grain. We investigated how two types of spatial scale affect a range of aggregate measures of β‐diversity and corresponding β ‐deviations, as well as the distance‐decay relationship (DDR). Variation in β ‐deviations was further partitioned into habitat heterogeneity, spatial aggregation and their joint effects across scales. Results Raw β‐diversity did not exhibit consistent trends with extent across metrics, but it consistently decreased with increasing grain. Both raw β‐diversity and β ‐deviations were strongly influenced by sampling effort. The decreasing trend in Sørensen differentiation ( q = 0) with increasing extent, predicted by theory, was removed after controlling for sampling effort. Notably, only abundance‐based measures showed a significant increase with spatial extent that was unaffected by sampling effort. Sørensen differentiation also decreased with increasing grain, contrary to theoretical expectations. The DDR was sensitive to grain size, and the proportion of variation in β ‐deviations explained by habitat heterogeneity increased with both spatial extent and grain. Main Conclusion The response of raw β‐diversity to extent depended on the metric used and was sensitive to sampling effort. Pairwise abundance‐based measures may provide a more reliable basis for cross‐scale comparisons. The DDR may only be able to capture scale‐specific ecological processes. Environmental filtering emerges as the dominant driver of community assembly at larger spatial scales, highlighting how analytical choices influence inference about assembly mechanisms.

Discovery of a novel compound against BmNPV using virtual screening based on the protein structure of the viral whole genome - Lin Zhang; Ying Ma; Junchi Hu; Feifei Liu; Yunxiang Jia; Peng Chen; Adrian Oo; Zhanqi Dong; Minhui Pan (Pesticide Biochemistry and Physiology, 2026)

A hybrid unsupervised-to-supervised machine learning framework for fracture segmentation in natural gas hydrate-bearing sediments - Zhi Liu; Yanlong Li; Ruijie Ye; Lin Dong; Minhui Qi; Wei Wang; Zikun Li; Fulong Ning; Nengyou Wu (Engineering Geology, 2026)

Long-term stabilization of realgar tailings via enhancing mineralogical transformation with microwave and FeSO4 treatment - Fengjiao Zhang; Zezhou Zhao; Yao Shi; Jiang Lin; Minhui Zheng; Anxu Sheng; Linling Wang; Xiaohui Wu; Jing Chen (Environmental Research, 2026)

Shadow under the lamp: Evidence-based assessments reveal local extirpation risk of large Indian civets (Viverra zibetha) concealed by intensive activity in human-dominated landscapes - Weiming Lin; Yue Weng; Hongmin Wang; Minhui Li; Qi Wang; Jia A; Qing Zhao; Fang Wang (Biological Conservation, 2026)

Coloring target and off-target effects of genetically modified nucleases by blue & white colony assays - Xumeng Chen; Li Xiao; Qian Wang; Lin Zhou; Yingying Xu; Cuilan Zhou; Minhui Dai; Fengjiao Wang; Huifen Xu; Dixian Luo; Pierre Sirois; Kai Li; et al. (Biotechnology Letters, 2025)

Effects of Nitrogen Deposition, Biodiversity and Climate on Productivity in a Large Temperate Forest Region - Jie Li; Senxuan Lin; Minhui Hao; Chunyu Fan; Juan Wang; Klaus von Gadow; Chunyu Zhang; Xiuhai Zhao (Global Ecology and Biogeography, 2025)
Aim Nitrogen deposition is a widespread global change driver that significantly affects terrestrial ecosystems. However, evidence on the specific mechanisms of productivity response to nitrogen deposition in temperate forests across ecological and climatic gradients is scarce. This study evaluates the effects of nitrogen deposition, multiple attributes of biodiversity and climate on productivity in a large temperate forest region. Location North‐eastern China. Time Period 2017. Major Taxa Studied Woody plants. Methods We assessed taxonomic, functional, and phylogenetic attributes of tree diversity and functional identity of forest communities across a wide range of ecological and climatic conditions. Using partial linear mixed models (LMMs), multivariate LMMs, and structural equation modelling, we investigated the effects and pathways of nitrogen deposition, biodiversity, and climate conditions on productivity. We also explored the relationship between nitrogen deposition and productivity across biotic and climatic gradients. Results Our results show that nitrogen deposition, phylogenetic diversity (PD), and the community‐weighted mean of maximum tree height (CWMHM) are significant positive drivers of productivity. Climate conditions primarily affected productivity indirectly through PD. In species‐poor high‐latitude forests characterised by cold and dry climates, nitrogen deposition had strong positive effects on productivity. That effect weakened towards warmer climatic conditions. Main Conclusions The findings of this study suggest that the response of productivity to nitrogen deposition depends on local ecological and climatic conditions. Our results underscore the importance of considering interactions among multiple global change drivers to improve the accuracy of ecosystem response predictions.

A leader-follower contrastive learning framework for imbalanced multimodal remote sensing image classification - Jia Li; Lin Zhao; Ping Tan; Minhui Zhao; Guoyun Zhang; Xinping Li (International Journal of Remote Sensing, 2025)

Pharmacokinetics and bioequivalence evaluation of two oral formulations of topiramate tablets in healthy Chinese male volunteers under fasting and fed conditions - Yamin Liu; Yubin Wang; Minhui Wang; Yaqin Wang; Ping Wu; Xiaocui Xia; Wanyu Wang; Lin Zhang; Pengfei Du; Jianbang Wu; Jie Shen; Yuanwei Jia (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

How sensory stimuli and barrier-free environments through restorative environmental perception influence visually impaired Individuals’ satisfaction with urban parks - Minhui Lin; Xinyun Lin; Yajun Wang (Landscape and Urban Planning, 2025)

Switchable transformation of biomass-derived furfural to furfuryl alcohol and isopropyl furfuryl ether over a zirconium-based bifunctional catalyst - Lei Hu; Baogang Sha; Yingxuan Shi; Na Shen; Minhui Yang; Keru Chen; Zhen Wu; Xing Tang; Aiyong He; Lu Lin (Chemical Engineering Journal, 2024)

Estimation on strength parameters of sediments with hydrate layered distribution based on triaxial shearing tests - Lin Dong; Nengyou Wu; Fang Liu; Zhiwen Sun; Minhui Qi; Gaowei Hu; Yanlong Li (Gas Science and Engineering, 2024)

Relationship between visitor characteristics, physical activity levels and park environment in subtropical areas’ urban parks - Minhui Lin; Xinyue Feng (Urban Forestry & Urban Greening, 2023)

Rational design of ordered porous nanoparticles for selective extraction of nitrobenzene compounds - Sheng Peng; Minhui Shen; Xiang Li; Yuan-Jun Tong; Jing Guo; Wei Lin; Yu-Xin Ye; Jianqiao Xu; Ningbo Zhou; Fang Zhu; Gangfeng Ouyang (Journal of Hazardous Materials, 2023)

Identification and characterization of Sox genes in the silkworm, Bombyx mori - Ling Wei; Daojun Cheng; Dong Li; Meng Meng; Lina Peng; Lin Tang; Minhui Pan; Zhonghuai Xiang; Qingyou Xia; Cheng Lu (Molecular Biology Reports, 2011)